Jurnal Kata: aggression or regression: a comparative study of heroines in the mill on the floss and pride and prejudice - Pyeaam abbasi (Prodi Bahasa Inggris Fak sastra PETRA, 2014)
the basic formula in the englist victorian novel seems to be an individual standing against the world